Comparação da fadiga muscular desenvolvida pelos músculos quadríceps femoral e deltóide médio e seu tempo de recuperação em pacientes com doença pulmonar obstrutiva crônica - Miranda, Eduardo Foschini (2010)
The peripheral muscle dysfunction is a common finding in patients with chronic obstructive pulmonary disease (COPD), the structural adaptations and functional impairment do not appear to be homogeneous between the muscles of the upper and lower limbs. The purpose of this study was to compare the fatigue developed by the quadriceps femoris (QF) and middle deltoid (MD) in patients with COPD and secondly, to analyze the time of recovery from fatigue between these muscles and muscle fatigue correlate with lung function and muscle QF and MD. We performed electromyographic evaluation of fatigue by the QF and MD median frequency (MF) and root mean square (RMS) to 60% of maximal voluntary contraction before and after the fatigue protocol in twenty one patients with COPD, we correct the muscle strength QF and MD for the muscle mass of both muscles. The main results were: (i) found reduced values of strength for the MD compared to QF, when adjusted for the maximum force the muscle mass that difference disappeared, (ii) when we correct the delta by the RQM and MF endurance time, we observed a significant difference between the fall of DMF/t for the QFF and MD and between the increase in DRQM/t for both muscles, (iii) there was no statistically significant difference for analysis of the recovery time of muscle fatigue among the QF muscles and MD. In conclusion, patients with chronic obstructive pulmonary disease have a higher fatigability of the upper limb in relation to the lower limb.